Perforation rate of appendicitis and negative appendectomies in children in Mankweng Hospital - Bhuiyan, Mirza MZU (Jour Med Resh and Health Sci, 2020)
Introduction: Appendectomy is a common emergency surgical procedure performed in children. Distances to surgical departments in Limpopo, delays in transportation impose unintentionally conservative initial managements before patients arrive at theatres. Aim: To find out how many children (under of age 15 years) had histologically proven appendicitis, how many had a normal appendix & what was the outcome of treatment in respect of mortality and wound infections. Method: A retrospective study from January 2004 to December 2007 carried out in the Mankweng Hospital. Cases of laparotomies for appendicitis of all children were retrieved from the hospital archives. Full blood count was done in all patients. Results: The total number of children included in this study was 71, male: 46, female: 25. Histology: acute appendicitis reported in 65 cases, mucocele 1, schistosomiasis 1 and normal appendix in 4 cases. White Blood Cell count was raised in 58 patients (56 in patients with appendicitis, 2 in patients with a normal appendix). Perforated appendix with peritonitis was found in 30 cases. Midline incision was done in 30 patients and local incisions in 41 cases. Wound infection occurred in 18 patients (25.35%). The time of referral to Mankweng hospital: 2 days to more than 7 days from the beginning of symptoms. Conclusions: Many paediatric patients with appendicitis in Limpopo Province came to Mankweng hospital very late; at least 2 days after symptoms began. The perforation rate of appendix was 42% and a normal appendix 5.63% .White Blood Count was raised in 86% in the group of patients with acute appendicitis and in 50% of those with a normal appendix